Properties of the pulsed plasma-liquid systems with acoustic waves focusing - Sidoruk, S.M.; Yukhymenko, V.V.; Chernyak, V.Ya.; Marchuk, V.E.; Gavrylyuk, E.Yu.; Martysh, E.V.; Fedorovich, O.A. (Вопросы атомной науки и техники, 2012)
The plasma-liquid system with cylindrical geometry and electric pulse discharge less than 10 microseconds duration was created. The influence of plasma treatment to water pH value was investigated. Dependences of the phenol destruction efficiency in its aqueous solution, as a model contaminant, from the solution concentration was obtained and got the best efficiency value: 20 eV per phenol molecule at its water solution with concentration 0.3 M. In obtained absorption spectra remnants of nitric and nitrous acids and other components was not observed, such components was observed after phenol aqueous solution destruction in similar DC plasma-liquid systems.